White spruce presence increases leaf miner effects on aspen growth in interior Alaska - Cahoon, Sean M. P.; Maher, Colin; Crawford, Daniel; Sullivan, Patrick F. (Frontiers in Forests and Global Change, 2024)
Alaska’s boreal forests are experiencing rapid changes in climate that may favor deciduous-dominated systems, with important implications for global biogeochemical and energy cycles. However, aspen (Populus tremuloides Michx.) has experienced substantial defoliation from the aspen leaf miner (Phyllocnistis populiella Cham., hereafter ALM) in Alaska, resulting in significant growth reductions. We conducted a tree-ring and Δ13C study to test the hypothesis that moisture limitation may have predisposed aspen to leaf miner damage. Contrary to our hypothesis, differences in climate-growth correlations between relatively severely and lightly affected trees were negligible during the pre-outbreak decades. Stands with greater summer precipitation had more limited ALM impact, however differences among models were small and multiple climate variables were suitable predictors of ALM impact. The strong negative relationship we detected between tree-ring Δ13C and basal area increment (BAI) suggested that interannual variation in Δ13C was driven primarily by variation in photosynthesis, limiting the utility of Δ13C as a tool to detect stomatal responses to moisture-limitation. Instead, we found that larger, faster-growing individuals on gentler slopes showed a stronger absolute reduction in BAI (pre-ALM BAI−post-ALM BAI), but were similar in relative BAI reduction (pre-ALM BAI/post-ALM BAI), with smaller, slower growing trees. Older trees and stands with greater relative abundance of white spruce [Picea glauca (Moench) Voss] had greater relative ALM impact whereas slower growing trees on steeper slopes were less affected. The significant effect of white spruce abundance on ALM impact was likely due to favorable leaf miner overwintering habitat provided beneath white spruce trees, which can lead to increased leaf miner survival and thus greater reductions in aspen growth. Our results illustrate the subtle but complex biotic interaction between microclimate and pest physiology in determining ALM-induced aspen growth reductions, adding important nuance to a hypothesized increase in deciduous tree cover in Alaska’s boreal forest.